2011
DOI: 10.1111/j.1360-0443.2011.03518.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of a stage 1 cognitive–behavioral trial to reduce alcohol use among human immunodeficiency virus‐infected out‐patients in western Kenya

Abstract: Aims Dual epidemics of HIV and alcohol use disorders, and a dearth of professional resources for behavioral treatment in sub-Saharan Africa, suggest the need for development of culturally relevant and feasible interventions. The purpose of this study was to test the preliminary efficacy of a culturally adapted 6-session gender-stratified group cognitive-behavioral therapy (CBT) intervention delivered by paraprofessionals to reduce alcohol use among HIV-infected outpatients in Eldoret, Kenya. Design Randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
179
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(185 citation statements)
references
References 45 publications
5
179
0
1
Order By: Relevance
“…The only comparable effort to develop a PT for alcohol problems in an LMIC was an effort to adapt CBT for alcohol use among HIV‐infected outpatients in Kenya (Papas et al., 2011). This study had several similarities with PREMIUM, for example, the substantial time spent on the development of the treatment; triangulation of data collected using mixed methods from diverse stakeholders; careful consideration of issues related to recruitment, training, competency evaluation, and maintenance of the counselors; and iterative use of data from the pilot study to refine the treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only comparable effort to develop a PT for alcohol problems in an LMIC was an effort to adapt CBT for alcohol use among HIV‐infected outpatients in Kenya (Papas et al., 2011). This study had several similarities with PREMIUM, for example, the substantial time spent on the development of the treatment; triangulation of data collected using mixed methods from diverse stakeholders; careful consideration of issues related to recruitment, training, competency evaluation, and maintenance of the counselors; and iterative use of data from the pilot study to refine the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A key difference was that while Papas and colleagues. (2011) started with an “off the shelf” treatment developed in Western settings, PREMIUM dismantled evidence‐based psychosocial treatments into their component strategies and added contextually appropriate strategies to create a pool of strategies which formed the basis for a new treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, potential participants in a Kenyan randomized trial who were HIV-positive reported a high prevalence of hazardous and binge drinking when screened by a separate investigator, whereas a much lower prevalence was reported (particularly by women) after screening was transferred to the clinic nurse. 67 On investigation, it was observed that the nurse was asking women: “You don't drink alcohol, do you?” and asking men: “How much alcohol do you drink?”, introducing interviewer bias. 68 Clinic staff and patients may be fearful of violating societal norms, and patients may be concerned that accurately reporting use of alcohol, non-adherence to ART, or risky sexual behaviors might jeopardize their access to treatment.…”
Section: Challenges and Opportunities For Hiv And Ncd Researchmentioning
confidence: 99%
“…Effective, evidencebased treatments for CMDs and SUDs provide psychosocial support and patient stability creating a recovery platform promoting good clinical outcomes for long term ART. These treatments include both psychosocial therapy and pharmacotherapy [80][81][82][83]. Integration of treatment for CMDs and SUDs into HIV care and treatment programs results in good clinical outcomes and is cost effective [76,[84][85][86][87].…”
Section: Services For Common Mental Disorders and Substance Use Disormentioning
confidence: 99%